Lyric poetry : the pain and the pleasure of words - Blasing, Mutlu Konuk, 1944- (Princeton University Press, 2007)
Lyric poetry has long been regarded as the intensely private, emotional expression of individuals, powerful precisely because it draws readers into personal worlds. But who, exactly, is the "I" in a lyric poem, and how is it created? In Lyric Poetry, Mutlu Blasing argues that the individual in a lyric is only a virtual entity and that lyric poetry takes its power from the public, emotional power of language itself. In the first major new theory of the lyric to be put forward in decades, Blasing proposes that lyric poetry is a public discourse deeply rooted in the mother tongue. She looks to po.